Scanning thermal microscopy for accurate nanoscale device thermography. (August 2021) - Gucmann, Filip; Pomeroy, James W.; Kuball, Martin
Highlights: Quantitative scanning thermal microscopy in PeakForce tapping mode on GaN/SiC HEMT. Transient thermal response of a nanothermocouple scanning thermal microscopy probe. Thermal time constant extraction of a nanothermocouple scanning thermal probe. Pixel-by-pixel calibration of scanning thermal probe verified by Raman thermography. Elimination of temperature artefacts in scanning thermal microscopy. Graphical Abstract: ga1 Abstract: We investigate the accuracy and reliability of temperature mapping using scanning thermal microscopy (SThM) in contact and PeakForce tapping mode on the example of a GaN-on-SiC high electron mobility transistor (HEMT). HEMT steady-state and transient surface temperatures are extracted from SThM measurements to study the method's accuracy and transient thermal response of the SThM probe; the results are verified by 3D finite element thermal simulation calibrated by Raman thermography. A reliable pixel-by-pixel calibration method to convert the measured electromotive force into surface temperature was developed. Discrete point measurements show good agreement (±3 °C) with the simulation in both contact and PeakForce tapping modes proving the feasibility of the SThM for accurate device thermography at the nanoscale. However, the measured temperature in calibrated 2D temperature maps deviates by as much as 15–44% from the simulation, suggesting the SThM probe did not reach the temperature steady state due to limitations in pixel dwell time during the recording of the 2D map.